2022
DOI: 10.1038/s41598-022-21345-7
|View full text |Cite
|
Sign up to set email alerts
|

CAMSAP2 promotes colorectal cancer cell migration and invasion through activation of JNK/c-Jun/MMP-1 signaling pathway

Abstract: CAMSAP2 has been reported to act as an oncogene in hepatocellular carcinoma. However, the expression CAMSAP2 and its potential roles in colorectal cancer remain unclear. In this study, qRT-PCR and immunoblotting analysis were used to detect the mRNA and protein levels of CAMSAP2 in colorectal cancer tissues and cell lines. Wound-healing, transwell migration and invasion assay were performed to determine whether CAMSAP2 promotes the capabilities of migration and invasion of colorectal cancer cells. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…One of them, TUBB3, was found to have a positive correlation with epithelial–mesenchymal transition, cell growth, and apoptosis in several CRC cell lines [ 30 , 31 ]. As a crucial part of the CRC-related JNK signaling pathway, JUN can be regulated by numerous upstream targets to further impact tumor growth, CRC cell invasion, and apoptosis [ 32 , 33 ]. In accordance with the results of our KEGG analysis, Yan et al recently found that in the IL-17 pathway, the deletion of the IL-17 receptor decreases the expression level of A20, which activates the JNK/c-JUN pathway and promotes tumor invasion, growth, and metastasis in patients with CRC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of them, TUBB3, was found to have a positive correlation with epithelial–mesenchymal transition, cell growth, and apoptosis in several CRC cell lines [ 30 , 31 ]. As a crucial part of the CRC-related JNK signaling pathway, JUN can be regulated by numerous upstream targets to further impact tumor growth, CRC cell invasion, and apoptosis [ 32 , 33 ]. In accordance with the results of our KEGG analysis, Yan et al recently found that in the IL-17 pathway, the deletion of the IL-17 receptor decreases the expression level of A20, which activates the JNK/c-JUN pathway and promotes tumor invasion, growth, and metastasis in patients with CRC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrin α 2 β 1 regulates self-renewal in prostate CSCs by interacting with ECM proteins, particularly collagen, to maintain the stem cell niche and support CSC self-renewal, facilitating tumor initiation by CSCs [91]. Integrin α 3 β 1 interaction with laminin activates signaling pathways, promotes CSC proliferation, and drives tumor growth and progression, thereby facilitating effective interaction of prostate CSCs with the tumor microenvironment, which is crucial for maintaining the stem cell niche and ensuring CSC maintenance and protection [95]. Integrin α 5 β 1 binds primarily to fibronectin, which is crucial for cell adhesion, migration, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that PLEKHA7 regulates LOX through miR-30c and MMP1 through miR-24 or miR-30c not directly, but through intermediate targets. One such intermediate target could be the JUN (cellular homolog of Jun avian sarcoma virus 17 proto-oncogene), which is responsible for MMP1 and LOX mRNA transcription (46)(47)(48)(49) and that we have previously shown to be suppressed by PLEKHA7 through miR-24 (10,11). Additional studies have also shown that miR-30 miRNAs suppress JUN (50).…”
Section: Mmp1 and Lox Are Directly And Indirectly Regulated By Plekha...mentioning
confidence: 97%